A Dynamic Model of Buy-Backs. (IMF Working Papers; Working Paper, 1989)
A dynamic framework is utilized to evaluate buy-backs of a country's external debt. The model solves for the price of debt on the basis of expectations concerning the debtor's ability to pay, and upon a variety of assumptions concerning changes in property rights consistent with various debt reduction programs. The importance of these assumptions is illustrated in simulations that relate debt reduction to a conventional balance of payments projection.